Landmarks in prostate cancer - Sathianathen, Niranjan J.; Konety, Badrinath R.; Crook, Juanita; Saad, Fred; Lawrentschuk, Nathan (Nature reviews. Urology, 2018)
The field of prostate cancer has been the subject of extensive research that has resulted in important discoveries and shaped our appreciation of this disease and its management. Advances in our understanding of the epidemiology, natural history, anatomy, detection, diagnosis, grading, staging, imaging, and management of prostate cancer have changed clinical practice and influenced guideline recommendations. The development of the Gleason score and subsequent modifications enabled accurate prediction of prognosis. Increased anatomical understanding and improved surgical techniques resulted in the development of nerve-sparing surgery for radical prostatectomy. The advent of active surveillance has changed the management of low-risk disease, and chemotherapy and hormonal therapy have improved the outcomes of patients with distant disease. Ongoing research and clinical trials are expected to yield more practice-changing results in the near future. In this Timeline article, the authors discuss studies that have improved our understanding of prostate cancer and influenced management of this disease.